The beginnings of crop phosphoproteomics: exploring early warning systems of stress - Rampitsch, Christof; Bykova, Natalia V. (Frontiers in Plant Science, 2012)
This review examines why a knowledge of plant protein phosphorylation events is important in devising strategies to protect crops from both biotic and abiotic stresses, and why proteomics should be included when studying stress pathways. Most of the achievements in elucidating phospho-signalling pathways in biotic and abiotic stress are reported from model systems: while these are discussed, this review attempts mainly to focus on work done with crops, with examples of achievements reported from rice, maize, wheat, grape, Brassica, tomato and soy bean after cold acclimation, hormonal and oxidative H2O2 treatment, salt stress, mechanical wounding or pathogen challenge. The challenges that remain to transfer this information into a format that can be used to protect crops against biotic and abiotic stresses are enormous. The tremendous increase in the speed and ease of DNA sequencing is poised to reveal the whole genomes of many crop species in the near future, which will facilitate phosphoproteomics and phosphogenomics research.